Impact of Hospitalization on Continuation of SGLT2 Inhibitors and GLP-1 Receptor Agonists for Comorbidities in Patients with Type 2 Diabetes - Bethany Murphy; Simran Chahal; Elleigh Shepherd; Nicole Taylor; Austin Camp (INNOVATIONS in Pharmacy)
Purpose: In the treatment of type 2 diabetes mellitus (T2DM), select sodium-glucose cotransporter 2 (SGLT2) inhibitors and glucagon-like peptide-1 (GLP-1) receptor agonists are recommended based on comorbidities such as chronic kidney disease (CKD), heart failure (HF), and atherosclerotic cardiovascular disease (ASCVD). Because guidelines typically recommend insulin for inpatient treatment of T2DM, there is potential these therapies may be negatively impacted by hospitalization. This study aimed to assess the effect of hospitalization on outpatient T2DM therapy.